Virtual animations applied to diffusion of architectural heritage. The village of Agreda (Soria) - Zaira Joanna Peinado Checa (Virtual Archaeology Review)
In recent decades there has been the development of so-called "new technologies" and have come to transform the traditional procedures for heritage diffusion, substantially expanding its possibilities, improving the quality, effectiveness, manageability and significantly reducing costs. In this article we want to highlight the spread of built heritage features applied to animations and virtual tours. To do this is to use the case study of cultural places of the village of Agreda (Soria) and also implemented for cataloging their heritage, using methods of architectural survey by photogrammetry and other digital procedures in those interest cultural real state.